Patented Automated Feeder Robot: Integrating Food and Water Dispensing, Camera System, and Wheeled Mobility - V., Jayaprakash; Kumar S.S, Aravind; J.R., Deepak; M., Anish; Nivin, Joy; J., Jayaprabakar (Recent Patents on Engineering, 2024)
<span class=
Keywords: servomotor